State-of-the-art methodological investigation of carotenoid activity and metabolism – from organic synthesis via metabolism to biological activity – exemplified by a novel retinoid signalling pathway. Issue 2 (23rd December 2022) - Bohn, Torsten; de Lera, Angel R.; Landrier, Jean-Francois; Carlsen, Harald; Merk, Daniel; Todt, Tilman; Renaut, Jenny; Rühl, Ralph
Abstract : Research strategy for carotenoids starting with causal data from epidemiological / supplementation studies via lab experiments, multi-omics analyses and final validation. Studies should preferably be done by a consortium of multiple expert groups. Abstract : Carotenoids are the most abundant lipophilic secondary plant metabolites and their dietary intake has been related to a large number of potential health benefits relevant for humans, including even reduced total mortality. An important feature is their potential to impact oxidative stress and inflammatory pathways, by interacting with transcription factors. For example, they may act as precursors of bioactive derivatives activating nuclear hormone receptor mediated signalling. These bioactive derivatives, originating e.g. from β-carotene, i.e. retinoids / vitamin A, can activate the nuclear hormone receptors RARs (retinoic acid receptors). Due to new analytical insights, various novel metabolic pathways were recently outlined to be mediated via distinct nuclear hormone receptor activating pathways that were predicted and further confirmed. In this article, we describe old and novel metabolic pathways from various carotenoids towards novel ligands of alternative nuclear hormone receptors. However, to fully elucidate these pathways, a larger array of techniques and tools, starting from organic synthesis, lipidomics, reporter models, classical in vitro and in vivo models and further omics-approaches and their statistical evaluation are needed to comprehensively and conclusively study this topic. Thus, we further describe state-of-the-art techniques from A to Ω elucidating carotenoid biological mediated activities and describe in detail required materials and methods needed – in practical protocol form – for the various steps of carotenoid investigations.